Density Estimation Assessment in Fluid State Based on Statistical Thermodynamics Perturbation Theory for Cyclo-Compounds - Haghighi, B.; Zeinali, S.; Zabeti, A.R.; Ghiamati, E.; Haghighi, Behnoud (Asian Journal of Chemistry, 2011)
In this paper, Ihm-Song-Mason (ISM) analytical equation of state (EoS) was employed to calculate the density of cyclo-compounds of cyclohexane, methyl cyclohexane, propyl cyclohexane, heptyl cyclohexane, cis-decalin, trans-decalin, cyclo pentane in fluid states. The best two available characteristic parameters of the Lennard-Jones (LJ) (12,6) potential were utilized to evaluate the second virial coefficients for each compounds required by the equation of state. As we know, the second virial coefficient is not very sensitive to the feature of the intermolecular potential so choosing the Lennard-Jones potential (12,6) for this propose is logical. Our previous results showed that the remaining parameters in the equation of state depend only on the repulsive part of the potential. The calculated second virial coefficients in conjunction to the other temperature-dependent parameters of the equation of state were employed to predict the density of cyclo-compounds. A comparison between the experimental values of density and the calculated values from Ihm-Song-Mason equation of state has been made. We found out that the agreement with experimental results is fairly good for all of the pertinent compounds.